Psychometric properties the Iranian version of Older People’s Quality Of Life questionnaire (OPQOL) - Maryam Nikkhah (Health and Quality of Life Outcomes, 2018)
Abstract Background Assessing quality of life (QOL) in elderly needs specific instruments. The Older People’s Quality of Life Questionnaire (OPQOL-35) is one of the common tools that used for measuring quality of life in elderly populations. The questionnaires contains 35 items tapping into eight domains including life overall, health, social relationships and participation, independence, control over life and freedom, home and neighborhood, psychological and emotional well-being, financial circumstances, culture and religion. This study aimed to translate and validate the OPQOL-35 in Iran. Methods Forward-backward procedure was applied to translate the original questionnaire from English into Persian. Then following qualitative face and content validity, a sample of elderly people completed the questionnaire. In order to evaluate the construct validity, exploratory and confirmatory factor analyses was performed. Subsequently, convergent and divergent validity of the factors were evaluated. Reliability was evaluated by performing internal consistency analysis and Intraclass Correlation Coefficients (ICC). Results In all 500 older people completed the questionnaire. The mean age of participant was 68.92 (SD = 6.97) years, and mostly were males (66.6%). The result of exploratory factor analysis showed 8 factors with Eigen values of greater than one, which explained 67.4% of the variance observed. Confirmatory factor analysis showed acceptable fit indexes for the data [Comparative Fit Index (CFI) = 0.92, Minimum Discrepancy Function by Degrees of Freedom divided (CMIN/DF) = 2.832, Root Mean Square Error of Approximation (RMSEA) = 0.067]. The convergent and divergent validity did not support three latent factors (Life overall, Independence, control over life, freedom and Psychological and emotional well-being). Convergent and divergent validity shown that construct fulfilled for the health, social relationships and participation, home and neighborhood, financial circumstances, culture and religion latent factors, however the results did not support the convergent and divergent validity for three latent factors (Life overall, Independence, control over life, freedom and Psychological and emotional well-being). Cronbach’s alpha coefficient for the subscales ranged from 0.65–0.95. Test-retest reliability (ICC) of the questionnaire with two weeks interval were ranged from 0.88–0.95 indicating a good range of reliability. Conclusion The findings suggest that the Iranian version of OPQOL-35 is a valid measure for assessing quality of life in elderly populations in different settings.